Penegakan Supremasi Hukum Dalam Al-Qur'an - Zaky Ismail (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2011)
This paper explores laws in the Qur’an, especially law enforcement. The theme of the supremacy of law enforcement in recent years increasingly crowded and exited. The increasing of intensity of this conversation can be understood because law enforcement is currently perceived as being more urgent thatn ever. In the supremacy of law enforcement effors at least there are three things that become the main focus, firstly, the principles that exist ans must be contained by the kegal materials (content of law) of how extent legal materials appriates and not contrary to mora values. Secondly, the legal structure of law and legal culture (culture of law) that contains the values of judtice and the principle of trust.